Rethinking the Thinking on Democracy in Education: What Are Educators Thinking (and Doing) About Democracy? - David Zyngier (Education Sciences, 2011)
This paper examines perspectives and perceptions of democracy of pre- and in-service teachers as well as teacher-education academics in Australia in order to develop a robust and critical democratic education. Using data from an on-line survey the paper presents the quantitative analyses, and the qualitative responses of contrasting understandings of democracy, citizenship and the role of education in the promotion and development of an active and thick democracy the paper critiques the neo-liberal (thin) democratic discourse of contemporary Australian academic research that suggests that the Civics and Citizenship Education project only requires some augmentation highlighting issues like sustainability and globalization while ignoring social justice issues. It begins by outlining the concepts of thick and thin democracy, and revisits the state of civics and citizenship education (CCE) in Australia. It is argued that while the pre-service teachers in this study may have a more critical and thicker understanding of democracy that is mirrored in the views of their teacher-education professors, the practicing teachers, on the other hand, have largely adopted the mainstream neo-liberal discourse, presenting a tendency to view democracy in a very narrow or thin way that may impact on their classroom practice. The paper concludes with recommendations related to what a thick democracy might actually look like in school education.